Case of Unusual Symptoms After L1 Compression Fracture Relieved by Muscle Energy Techniques (MET) and Tender Point Acupressure - Ju, Kwi Suk; Kim, Yun Gyong; Ri, Mok Ran; Kim, Un Mi (Medical Science Journal for Advance Research, 2026)
Background: This case had a 4 years long lasting story of unusual symptoms of penile cold paresthesia and pain, perianal tinglingin addition to severe back pain and physical examination showed Sacroiliac joint dysfunction after L1 compression fracture. Vertebral compression fracture may usually result low back pain, limited movement, kyphosis, lower extremity pain, and weakness, urinary dysfunction or urinary incontinence. But the symptoms of the cold paresthesia and pain of penis as well as perianal tingling are uncommon after L1 compression fracture, it is why we report this case. Conclusion: MET to the sacral torsion combined with tender point acupressure along by the nerve may benefit unusual symptoms after L1 compression fracture.